2012
DOI: 10.14417/ap.282
|View full text |Cite
|
Sign up to set email alerts
|

Grupo de suporte para mulheres de veteranos de guerra: Um estudo qualitativo

Abstract: As consequências dos episódios traumáticos vividos em teatro de guerra afectam não só a vítima directa mas também a esposa/companheira do próprio veterano. A intervenção psicológica junto das mulheres dos veteranos é importante a dois níveis: por um lado porque estas mulheres apresentam psicopatologia e dificuldades na relação conjugal. Por outro lado, a recuperação do próprio veterano é facilitada através da melhoria da sua relação marital que contribui de forma significativa para a redução da sintomatologia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Taking into account the clinical characteristics of PTSD, together with psychological morbidity, is not surprising that marital relationship and sexual life may be impaired, in this population (Bentsen et al, 2015;Goff et al, 2007). As war veteran's couples experience low levels of marital satisfaction and high levels of conflict, poor problem resolution and communication difficulties (Cook et al, 2004;Pereira & Pedras, 2010), it comes as no surprise that these couples may present intimacy problems and low sexual satisfaction (Ahmadi et al, 2006;Cook et al, 2004). In terms of the duration of the marital relationship, it makes intuitive sense that veterans who have been married for a shorter period of time reported less dissatisfaction as the relationship may be less worn out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the clinical characteristics of PTSD, together with psychological morbidity, is not surprising that marital relationship and sexual life may be impaired, in this population (Bentsen et al, 2015;Goff et al, 2007). As war veteran's couples experience low levels of marital satisfaction and high levels of conflict, poor problem resolution and communication difficulties (Cook et al, 2004;Pereira & Pedras, 2010), it comes as no surprise that these couples may present intimacy problems and low sexual satisfaction (Ahmadi et al, 2006;Cook et al, 2004). In terms of the duration of the marital relationship, it makes intuitive sense that veterans who have been married for a shorter period of time reported less dissatisfaction as the relationship may be less worn out.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed marital satisfaction to be problematic in war veterans (Jordan et al, 1992;Wilson et al, 2004) but it seems that it is the quality of the marriage that influences, positively or negatively, mental health (Levenson et al, 1993). Furthermore, since research shows (Pereira & Pedras, 2010) that the veterans' generation culturally believes that marriage is for life, and that women need to be available and sexually satisfy their husbands, as part of their role as good wives due to the greater influence of the catholic church (the colonial war had a missionary goal), one may hypothesize that when the veteran feels dissatisfied regarding the marriage, he may feel depressed and his sexual life becomes affected, as a result. In addition, marital dissatisfaction mediated the relationship between number of PTSD symptoms and sexual dissatisfaction, emphasizing once again the role of the quality of the marital relationship, between number of PTSD symptoms and sexual dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation